Human Beings Trafficking. the Albanian Legislation - Hasani, Nikolin (European Journal of Multidisciplinary Studies, 2016)
Human trafficking has emerged as a negative phenomenon, with a large multiple social risks, primarily based on human rights violations practices, on the continuous victimization of people and the denial of human dignity. Economic recession, cultural and rural families, tin heterogeneity of the urban population are also other factors which facilitate domestic trafficking. Albania’s geographical position at the external borders of the EU is a mitigating factor for Albanians and other populations in the region to move towards Europe illegally. The aim of this paper is to presents the legal aspects of trafficking in human beings in Albania after the communism regime.